FUNGSI ACCOUNT RECEIVABLE TERHADAP KELANCARAN ARUS KAS DI FAIRFIELD BY MARRIOT SURABAYA - Lexi Pranata Budidharmanto, Lexi Pranata Budidharmanto; Deviyanti Lunardi, Deviyanti Lunardi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Abstract Types of receipts at hotels can be divided into cash receipts and receivables where guests who come can come from individuals and companies. Cash payments can also be through bank transfers from a savings account or through a credit card. The continuity of the hotel business is very dependent on the smooth reception of all guests. The challenge occurs when the receivables are due but there is no repayment, or only partial payment is paid so that the Account Receivable plays a very important role in the smooth flow of cash and a review of the receiveable account function is needed for the smooth flow of cash at the Fairfield by Marriott Hotel Surabaya. Using a simple philosophy of phenomenology that is descriptive, three informants from the finance department were determined through in-depth interviews and researcher involvement during the apprenticeship process, the results of which were triangulated with theories on which thinking was based. It was found that the reality on the ground in accordance with the existing theory is that receivable accounts can convert hotel receivables into cash which is an important source of revenue and can be used for operational costs for hotels. If the hotel finances begin to be unhealthy, then it is because there are problems with financial performance, and if this happens continuously the hotel will bear the possibility of losses. The receiveable account section should pay special attention to preparing a billing schedule, making provisions for payments, and providing an assessment of the debtor so that management can determine further strategic steps in maintaining the financial health condition of the company.